Dioecious hemp (Cannabis sativa L.) plants do not express significant sexually dimorphic morphology in the seedling stage - Lesley G. Campbell (Nature Portfolio, 2021)
Abstract Some economically important crop species are dioecious, producing pollen and ovules on distinct, unisexual, individuals. On-the-spot diagnosis of sex is important to breeders and farmers for crop improvement and maximizing yield, yet diagnostic tools at the seedling stage are understudied and lack a scientific basis. Understanding sexual dimorphism in juvenile plants may provide key ecological, evolutionary and economic insights into dioecious plant species in addition to improving the process of crop cultivation. To address this gap in the literature, we asked: can we reliably differentiate males, females, and co-sexual individuals based on seedling morphology in Cannabis sativa, and do the traits used to distinguish sex at this stage vary between genotypes? To answer these questions, we collected data on phenotypic traits of 112 C. sativa plants (50 female, 52 male, 10 co-sexuals) from two hemp cultivars (CFX-1, CFX-2) during the second week of vegetative growth and used ANOVAs to compare morphology among sexes. We found males grew significantly longer hypocotyls than females by week 2, but this difference depended on the cultivar investigated. Preliminary evidence suggests that co-sexual plants may be distinguished from male and female plants using short hypocotyl length and seedling height, although this relationship requires more study since sample sizes of co-sexual plants were small. In one of the cultivars, two-week old male plants tend to produce longer hypocotyls than other plants, which may help to identify these plants prior to anthesis. We call for increased research effort on co-sexual plants, given their heavy economic cost in industrial contexts and rare mention in the literature. Our preliminary data suggests that short hypocotyl length may be an indicator of co-sexuality. These results are the first steps towards developing diagnostic tools for predicting sex using vegetative morphology in dioecious species and understanding how sexual dimorphism influences phenotype preceding sexual maturity.